Epidemiological parameters to delineate weather-disease interactions and host plant resistance against leaf blight in small cardamom (Elettaria cardamomum Maton) - R Gowri, C N Biju, M F Peeran,; S J Ankegowda, R Praveena, A Sharon, (Journal of Spices and Aromatic Crops, 2018)
Small cardamom, the versatile spice of Zingiberaceae is cultivated in diverse agro-climatic regions of India especially in South India. Leaf blight incited by Colletotrichum gloeosporioides sensu lato is one among the major challenges encountered across different cardamom growing tracts. In the present investigation, epidemiology of cardamom leaf blight was studied and an attempt was made to decipher the resistant nature of Malabar, Mysore and Vazhukka genotypes based on epidemiological parameters. The average percent disease index recorded in Malabar, Mysore and Vazhukka varied from 23.41 to 27.72, 18.79 to 20.34 and 18.74 to 20.38, respectively. The disease exhibited a positive correlation with respect to Tmax and Tmin in all the genotypes, however, significant correlation was observed only in Malabar and Mysore with respect to Tmax. Whereas, rainfall and rainy days had negative correlation with leaf blight in all genotypes however found to be non-significant. The average infection rate was maximum (0.000429) in Malabar, whereas it was 0.000124 and 0.000186 in Mysore and Vazhukka, respectively. The area under disease progress curve registered the highest for Malabar (8814.15) and lowest in Vazhukka (6531.02) while, Mysore type recorded 6612.96 indicating that, Vazhukka and Mysore types might posses horizontal resistance and Malabar with vertical resistance. In the light of above results, plant protection measures could be scheduled based on the take-off level and genotypes with horizontal resistance could be promising candidates in resistance breeding programmes.